Berberine Facilitates Extinction of Drug-Associated Behavior and Inhibits Reinstatement of Drug Seeking - Shen, Xi; Hui, Rongji; Luo, Yixiao; Yu, Hailei; Feng, Suiyuan; Xie, Bing; Bi, Haitao; Galaj, Ewa; Cong, Bin; Ma, Chunling; Wen, Di (Frontiers in Pharmacology, 2020)
A high rate of relapse is a major clinical problem among drug-addicted individuals. Persistent traces of drug-associated reward memories contribute to intense craving and often trigger relapse. A number of interventions on drug-associated memories have shown significant benefits in relapse prevention. Among them are pre- or post-extinction pharmacological manipulations that facilitate the extinction of drug-associated behavior. Berberine, a bioactive isoquinoline alkaloid, has been recently reported to provide therapeutic benefits for a number of central nervous system (CNS) disorders, including morphine addiction. The present study aimed to investigate whether berberine could serve as a post-extinction pharmacological intervention agent to reduce risks of reinstatement of drug seeking. We found that an intragastric administration of berberine at doses of 25 and 50 mg/kg during the critical time window significantly facilitated the extinction of morphine-reward related behavior in free access and confined conditioned place preference (CPP) extinction paradigms, and subsequently it prevented reinstatement and spontaneous recovery of morphine-induced CPP in mice. Intriguingly, the berberine treatment with or without extinction training altered expression of plasticity-related proteins such as brain-derived neurotrophic factor (BDNF), AMPA receptors (GluA1 and GluA2) in the nucleus accumbens (NAc). Moreover, the post-extinction berberine treatment significantly reduced reinstatement of cocaine-induced CPP and operant intravenous self-administration (IVSA) memories in rats. Altogether, our findings suggest that extinction training combined with the post-extinction berberine treatment can facilitate extinction of drug-associated behavior making it an attractive therapeutic candidate in relapse prevention.